33. The role of intraoperative neurophysiology in scoliosis surgery. Issue 12 (December 2017) - Costa, P.; Borio, A.; Marmolino, S.; Mogno, M.; Serpella, D.; Girardo, M.; Di Ruocco, C.; Cinnella, P.; Aleotti, S.
Abstract : The onset of neurological deficit is the most feared complications in surgical correction of spine deformities. Aim of this study is to assess the value of intraoperative neurophysiologic monitoring during scoliosis surgery. 173 scoliosis surgeries in 164 patients were monitored with muscle-motor evoked potentials (m-MEPs) and peripheral and cortical upper and lower limb Somatosensory Evoked Potentials (SEPs). In 45 surgeries, thoracic and lumbar pedicle screws were neurophysiologically tested by triggered-EMG. The overall monitor ability was 98.3%. Significant intraoperative modification occurred in 26 surgeries (15%). In 11 cases (6.4%) changes were consistent with spinal cord damage, in 6 (6.9%) with brachial plexopathy. Finally, three patients (1.7%) presented transient disappearance of four limbs MEPs and SEPs due to a pharmacological effect. 2 patients (1.2%) awaked with a brachial plexopathy: they all completely recovered within 3 months. In one patients, an intraoperative persistent disappearance of unilateral lower limb MEPs and SEPs was associated with a postoperative severe monoparesis: therefore, the rate of new neurological deficit was 0.6%. Intraoperative neurophysiology may provide a valuable biomarker in detection of impending central and/or peripheral nervous system injury at a reversible stage.